Reversible uncoupling of oxidative phosphorylation at low oxygen tension. - Kramer, R S (1983)
The stoichiometry of oxidative phosphorylation at low oxygen tension (less than 3 torr; O2 less than 5 microM) has been measured in rat liver mitochondria. In a steady-state model in which respiration rate was experimentally controlled by either oxygen or substrate (succinate) limitation, flux-dependent variation in the phosphorylation efficiency (P/O ratio) of stimulated mitochondrial respiration was evaluated. P/O ratio remained constant over a wide range of respiration rates in mitochondria limited only by substrate availability. In contrast, oxygen-limited mitochondria demonstrated a continuous decline in P/O ratio as respiration was increasingly restricted. Significant differences in the two test conditions were demonstrated throughout the range of analysis. The effect of oxygen limitation on phosphorylation efficiency was shown to be completely reversed by restoring zero-order kinetics associated with high oxygen tension. These findings are discussed in regard to a proposed uncoupling of mitochondrial coupling site II at low oxygen tension arising as a consequence of energy-dissipating electron flux through the ubiquinone-cytochrome b-c1 region of the respiratory chain (complex III).